The association between weight change patterns and obesity-related complex multimorbidity: evidence from NHANES - Gong, Hong-Jian; Tang, Xingyao; Zhou, Jian-Bo (Frontiers in Endocrinology, 2024)
Objectives: Obesity is a major risk factor for non-communicable diseases (NCDs), which has been the leading cause of death nowadays. This study is aimed to examine the association between total changes in BMI across adulthood and the risk of obesity-related complex multimorbidity in elderly, characterizing the capacity of BMI waves in the predicting of major chronic diseases. Methods: In this retrospective study, 15 520 participants were analyzed from the National Health and Nutrition Examination Survey (NHANES) from 1999 and 2018. Body mass index (BMI) was categorized as obesity (≥30.0 kg/m²), overweight (25.0–29.9 kg/m²), normal weight (18.5–24.9 kg/m²), and underweight (<18.5 kg/m²). Odds ratios (ORs) with 95% confidence interval (CIs) for relationship between BMI change patterns and major health outcomes included hypertension, cancer, chronic obstructive pulmonary disease, cardiovascular disease and diabetes and population attributable fractions (PAFs) of BMI was evaluated. Results: In comparison with participants who remained at non-obese, those stable obese showed highest risks of developing at least one chronic disease in later life, with odds ratios of 2.76 (95% CI: 2.20 to 3.45) from age 25 years to 10 years before baseline, 2.90 (2.28 to 3.68) from age 25 years to baseline, and 2.49 (2.11 to 2.95) in the 10-year period before baseline. Moving from the non-obese to obese weight-change pattern in all periods (from age 25 years to 10 years before baseline: OR = 1.82; 95% CI, 1.57 to 2.11; from age 25 years to baseline: OR = 1.87; 95% CI, 1.59 to 2.19; from 10 years before baseline to baseline: OR = 1.62; 95% CI, 1.26 to 2.08) and moving from obese to non-obese the 10-year period before baseline (OR=1.89; 95% CI, 1.39 to 2.57) was associated with increased risk of chronic diseases. Midlife obesity status can explain 8.6% risks of the occurrence of the chronic diseases in elderly. Conclusions: Maintaining stable healthy weight as well as weight loss in early adulthood and midlife is important for life quality in the ageing process. More effective strategies and policies to reduce the prevalence of obesity is needed.